1998
DOI: 10.1097/00004714-199812000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response to Lithium and Carbamazepine in the Prophylaxis of Bipolar Disorder

Abstract: In a randomized, prospective, multicenter study with an observation period of 2.5 years, the differential prophylactic efficacy of lithium versus carbamazepine was compared in 171 patients fulfilling DSM-IV criteria for bipolar disorder. Serum drug levels were 0.6+/-0.1 mmol/L for lithium and 6.1+/-1.3 microg/mL for carbamazepine. Patients were subdivided into a classical subgroup (bipolar I patients without mood-incongruent delusions and without comorbidity, N = 67) and a nonclassical subgroup including all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(101 citation statements)
references
References 23 publications
1
91
0
9
Order By: Relevance
“…Furthermore, clinical variables such as episode sequence (Kokopolus et al, 1980;Maj et al, 1989), frequency of mood cycling (Dunner and Fieve, 1974;Bowden 1995;Denicoff et al, 1997), presence of mood-congruent or -incongruent psychotic features of the index episode (Greil et al, 1998;Tohen et al, 1992), comorbid conditions (especially anxiety disorders) (Greil et al, 1998;Feske et al, 2000), and family history (Grof et al, 1994) may provide further explanation of the differential response to lithium and divalproex. Some of these may need to be described in future studies as potential explanatory factors of treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, clinical variables such as episode sequence (Kokopolus et al, 1980;Maj et al, 1989), frequency of mood cycling (Dunner and Fieve, 1974;Bowden 1995;Denicoff et al, 1997), presence of mood-congruent or -incongruent psychotic features of the index episode (Greil et al, 1998;Tohen et al, 1992), comorbid conditions (especially anxiety disorders) (Greil et al, 1998;Feske et al, 2000), and family history (Grof et al, 1994) may provide further explanation of the differential response to lithium and divalproex. Some of these may need to be described in future studies as potential explanatory factors of treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…A later, naturalistic study revealed that approximately 30% of lithium-treated bipolar patients experienced depressive relapse yearly (O'Connell et al, 1991). Lithium has been found to be more effective in the maintenance treatment of 'classical' rather than 'nonclassical' bipolar disorder (Greil et al, 1998), and less effective in rapid cycling, for which several anticonvulsants appear to be more effective (Dunner and Fieve, 1974;Bauer et al, 1994;Calabrese et al, 2000). Antidepressants are frequently prescribed for bipolar depression prophylaxis (Zarate et al, 1995); however, their use is controversial because they may induce mood destabilization (Altshuler et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It also remains common for trials to enrol patients with both BDII and BDI without reporting results separately, making it difficult to determine if there are clinically meaningful differences in treatment response between the two illnesses. This is important because, while clinical experience and the results of many studies suggest that response to mood stabilizers and antipsychotics is similar in BDII and BDI, there are enough exceptions to suggest this should not be taken for granted 248, 405, 431. This is also the case for antidepressants, which may have a more favourable risk‐benefit ratio in BDII (reviewed below).…”
Section: Bipolar II Disordermentioning
confidence: 99%
“…For example, in a randomized study in bipolar patients 32 observing the effects of carbamazepine versus lithium versus placebo, lithium was superior in preventing episodes requiring hospitalization in classic bipolar I patients, but there was a trend favoring carbamazepine for bipolar variants. Lithium was superior to carbamazepine in another notable randomized bipolar trial.…”
Section: Carbamazepinementioning
confidence: 99%